2021
DOI: 10.3389/fcell.2021.700006
|View full text |Cite
|
Sign up to set email alerts
|

MiR-665 Regulates Vascular Smooth Muscle Cell Senescence by Interacting With LncRNA GAS5/SDC1

Abstract: Background: Vascular aging is considered a special risk factor for cardiovascular diseases, and vascular smooth muscle cells (VSMCs) play a major role in aging-related vascular remodeling and in the pathological process of atherosclerosis. Recent research has reported that long non-coding RNA/microRNA (lncRNA/miRNA) is a critical regulator of cellular senescence. However, the role and mechanism of lncRNA GAS5/miR-665 axis in VSMC senescence remain incompletely understood.Methods: Cellular senescence was evalua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 35 publications
0
14
0
Order By: Relevance
“…Li et al [64] revealed that the expression of GAS5 increased in atherosclerotic mouse plaques, and GAS5 knockout promoted endothelial cell proliferation, reduced apoptosis, and improved AS. Chen et al [65] revealed that GAS5 is related to the aging of smooth muscle and plays a role in the pathological process of AS. H19, a lncRNA that was among the first to be discovered and studied, has also been reported to be involved in cardiovascular diseases, CHD, and AS.…”
Section: Discussionmentioning
confidence: 99%
“…Li et al [64] revealed that the expression of GAS5 increased in atherosclerotic mouse plaques, and GAS5 knockout promoted endothelial cell proliferation, reduced apoptosis, and improved AS. Chen et al [65] revealed that GAS5 is related to the aging of smooth muscle and plays a role in the pathological process of AS. H19, a lncRNA that was among the first to be discovered and studied, has also been reported to be involved in cardiovascular diseases, CHD, and AS.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, GAS5 can regulate proliferation and senescence of EPCS through modulation of the PI3K/AKT signaling ( Yao et al, 2019 ). Another study has indicated that suppression of miR-665 by GAS5 modulates VSMC senescence through down-regulating SDC1 ( Chen et al, 2021a ). GAS5 has also been shown to be differentially expressed between young and old mouse brain samples, indicating its putative impact on senescence and brain aging.…”
Section: Lncrnas and Senescencementioning
confidence: 99%
“…Some lncRNAs, such as lncRNA GAS5, can affect VSMC senescence by acting as ceRNA and affect the pathological process of AS [71]. Knockdown of Linc00299 also inhibits ox-LDL damage to T/GHA-VSMC due to regulation of the miR-135a-5p/XBP1 axis in AS [72].…”
Section: | Tgf-β Signaling Pathway Affected By Lncrnas Sponging Mirna...mentioning
confidence: 99%